2022
DOI: 10.3389/fnhum.2022.981366
|View full text |Cite
|
Sign up to set email alerts
|

Two modes of being together: The levels of intersubjectivity and human relatedness in neuroscience and psychoanalytic thinking

Abstract: The notion of intersubjectivity has achieved a primary status in contemporary psychoanalytic debate, stimulating new theoretical proposals as well as controversies. This paper presents an overview of the main contributions on inter-subjectivity in the field of neurosciences. In humans as well as—probably—in other species, the ability for emotional resonance is guaranteed early in development. Based on this capacity, a primary sense of connectedness is established that can be defined inter-subjective in that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…As far as inhibitory control is concerned, several studies have shown that this executive function is required for perspective taking [86]. The literature on the theory of the mind showed that a capacity for self-other differentiation and intersubjective connection can be established only if the inhibition of the default mode of self-centered interpretation of interactions is achieved [87,88]. This study seems indeed to point to the relevance of the consolidation of inhibitory control occurring in the course of adolescence for the possibility to further develop an intersubjective exchange from this phase of development on.…”
Section: Discussionmentioning
confidence: 99%
“…As far as inhibitory control is concerned, several studies have shown that this executive function is required for perspective taking [86]. The literature on the theory of the mind showed that a capacity for self-other differentiation and intersubjective connection can be established only if the inhibition of the default mode of self-centered interpretation of interactions is achieved [87,88]. This study seems indeed to point to the relevance of the consolidation of inhibitory control occurring in the course of adolescence for the possibility to further develop an intersubjective exchange from this phase of development on.…”
Section: Discussionmentioning
confidence: 99%